Content Delivery and Vertical Integration in O-L Content Markets - Diego Lanzi; Massimiliano Marzo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
On-line content delivery and vertical alliances between conduit and content providers are nowadays crucial issues in digital markets. In this paper, we discuss and compare a push and a pull model for on-line content delivery in the case of non-zero marginal cost for network transits because of network services for content delivery (like data caching). Under both models, we show that rationales for vertical strategic integration between conduit and content providers phase out in successive monopolies and Bertrand duopolies.
Keywords: 330; Internetbasierter Dienst; Vertikale Integration; Duopol